Outcome of Endoscopic Sphenopalatine Artery Cauterization for Posterior Epistaxis - Kharel, Bijaya; Gurung, Urmila; Tripathi, Prashant; Rayamajhi, Pabina; Silwal, Priyansha (Journal of Institute of Medicine Nepal, 2019)
Introduction: Epistaxis is a common otorhinolaryngology emergency condition. Majority of it is anterior epistaxis which usually improves with conservative management. However, for posterior epistaxis, apart from posterior nasal packing, endoscopic sphenopalatine artery cauterization (ESPAC) is considered an effective measure for its control. Hence, this study was conducted to evaluate the outcome of endoscopic sphenopalatine artery cauterization for posterior epistaxis.Methods: Retrospective medical chart review of patients who underwent endoscopic sphenopalatine artery cauterization for posterior epistaxis from January to December 2018 at Ganesh Man Singh Memorial Academy of ENT-Head & Neck Surgery, Tribhuvan University Teaching Hospital, Kathmandu, Nepal.Results: A total of 31 patients (21 males and 10 females) underwent ESPAC during the one-year period. Twenty-seven of them were unilateral whilst four were bilateral. Four of them rebled, of which two bled within 48 hours and the remaining two after two months. The overall success rate of ESPAC was 87.1% (27/31).Conclusion: Endoscopic sphenopalatine artery cauterization is an effective measure to control posterior epistaxis.